Die Bedeutung monetärer Größen für die deutsche Wachstumsschwäche 1995 -2005 - Jonas Dovern; Nils Jannsen; Joachim Scheide (Kiel Institute for the World Economy (IfW), 2009)
Between 1995 and 2005, the German economy has experienced a phase of weak economic growth. We analyze whether this weak growth performance can be attributed to the stance of monetary conditions during that period. We show that the real effective exchange rate did have almost no dampening effects on growth. On the contrary, the introduction of the euro and the single monetary policy for the euro area seems to have contributed significantly to the low trend growth rate in Germany between 1999 and 2005.
Keywords: E32; E52; E58; F31; 330; Weak growth; monetary conditions; monetary policy; real exchange rate; EMU; Wirtschaftswachstum; Europäische Wirtschafts- und Währungsunion; Geldpolitik; Kaufkraftparität; Monetärer Indikator; Deutschland